Late-onset cervicoscapular muscle atrophy and weakness after radiotherapy for Hodgkin disease: a case series. Issue 1 (17th December 2009) - Furby, A; Béhin, A; Lefaucheur, J-P; Beauvais, K; Marcorelles, P; Mussini, J-M; Bassez, G; Créange, A; Eymard, B; Pénisson-Besnier, I
Abstract : Patients with cervical or mediastinal Hodgkin disease (HD) classically underwent chemotherapy plus extended-field radiation therapy. We report six patients who gradually developed severe atrophy and weakness of cervical paraspinal and shoulder girdle muscles 5–30 years after mantle irradiation for HD. Although clinical presentation was uniform, including a dropped head syndrome, electrophysiological and pathological findings were rather heterogeneous. Either neurogenic or myogenic processes may be involved and sometimes combined. We discuss the pathophysiological mechanisms underlying these cervicoscapular motor complications of mantle irradiation in HD.